2011
DOI: 10.1093/icvts/ivr028
|View full text |Cite
|
Sign up to set email alerts
|

Does surgical stabilization improve outcomes in patients with isolated multiple distracted and painful non-flail rib fractures?

Abstract: A best evidence topic was constructed according to a structured protocol. The question addressed was whether surgical stabilization is effective in improving the outcomes of patients with isolated multiple distracted and painful non-flail rib fractures. Of the 356 papers found using a report search, nine presented the best evidence to answer the clinical question. The authors, journal, date and country of publication, study type, group studied, relevant outcomes and results of these papers are given. We conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 12 publications
(10 reference statements)
0
29
0
7
Order By: Relevance
“…In our study, we found a difference between the early surgery group and conservative follow up group in favor of the surgery (p= 0.020). The rate of pneumonia in these patients who did not require intensive care support was much lower than the patients who did not undergo surgery [8,19,20]. However, these studies generally include ICU patients and as we mentioned before, these patients have different risks and intensive care support is a predisposing factor for septic complications.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found a difference between the early surgery group and conservative follow up group in favor of the surgery (p= 0.020). The rate of pneumonia in these patients who did not require intensive care support was much lower than the patients who did not undergo surgery [8,19,20]. However, these studies generally include ICU patients and as we mentioned before, these patients have different risks and intensive care support is a predisposing factor for septic complications.…”
Section: Discussionmentioning
confidence: 99%
“…We think the health status of the group III is better than the other groups. There are texts in the literature recommending rib fixation to reduce the pain of the patient if the fracture ends are moving in multiple and displaced rib fractures, even if they do not have flail chest [18].…”
Section: Discussionmentioning
confidence: 99%
“…Titanium can integrate with bone. This is reliant on osteoblasts attaching to the titanium surface and eventually forming mineralized bone in continuity with the implant, which then is less likely to "loosen" over time (9,11).…”
Section: Discussionmentioning
confidence: 99%